2023
DOI: 10.3389/fendo.2023.1127676
|View full text |Cite
|
Sign up to set email alerts
|

Total versus partial adrenalectomy in bilateral pheochromocytoma – a systematic review and meta-analysis

Abstract: BackgroundIn patients with bilateral pheochromocytoma, partial adrenalectomy offers the chance to preserve adrenal function and avoid the need for lifelong steroid supplementation. However, the risk of tumour recurrence raises questions about this procedure. The aim of our study was to compare partial and total adrenalectomy in bilateral pheochromocytoma through a systematic review with meta-analysis.MethodsA systematic search was carried out using databases (MEDLINE, EMBASE, Scopus, Web of Science, CENTRAL) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
2
0
2
Order By: Relevance
“…The report concluded that the sample was moderately differentiated with background nodular hyperplasia of the adrenal cortex. In the context of ACTH‐secreting phaeochromocytomas (which are rare), 18,26,27 current evidence supports surgical resection of the involved and contralateral adrenal glands if there is bilateral disease 18,26–28 …”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The report concluded that the sample was moderately differentiated with background nodular hyperplasia of the adrenal cortex. In the context of ACTH‐secreting phaeochromocytomas (which are rare), 18,26,27 current evidence supports surgical resection of the involved and contralateral adrenal glands if there is bilateral disease 18,26–28 …”
Section: Discussionmentioning
confidence: 93%
“…In the context of ACTH-secreting phaeochromocytomas (which are rare), 18,26,27 current evidence supports surgical resection of the involved and contralateral adrenal glands if there is bilateral disease. 18,[26][27][28] Pregnancy in patients with CS poses a diagnostic and therapeutic challenge. Due to the limited literature, management is often individualised and dependent upon maternal and fetal factors.…”
Section: Discussionmentioning
confidence: 99%
“…Eine Metaanalyse aus 25 Studien mit insgesamt 1444 Patientinnen und Patienten kommt zu einem ähnlichen Ergebnis: Nach Erhalt der Nebennierenrinde im Rahmen einer bilateralen Entfernung von Phäochromozytomen besteht zwar prinzipiell ein erhöhtes Rezidivrisiko, jedoch ist das Risiko einer Metastasierung und die Gesamtsterblichkeit im Vergleich zur vollständigen bilateralen Adrenalektomie vergleichbar. Dagegen überwiegt der Vorteil eines Funktionserhaltes bei Belassen der Nebennierenrinde deutlich [ 39 ]. Eine aktuelle internationale Leitlinie zu Patientinnen und Patienten mit SDH-B -Mutation rät in dieser Patientengruppe allerdings dringend von einer organerhaltenden Operation ab, da hier das Malignitätsrisiko mit teilweise über 50 % doch beträchtlich ist.…”
Section: Rolle Der Parenchymerhaltenden Nebennierenresektion Bei Bila...unclassified
“…В ходе анализа было отмечено, что риск развития рецидива основного заболевания после частичной адреналэктомии был значительно выше, чем после тотальной адреналэктомии (OР 3,72, 95% ДИ 1,54-8,96, р = 0,003). Тем не менее статистически значимой разницы в риске развития метастазов и в показателях общей выживаемости в группе пациентов с двусторонними ФХ, перенесших тотальную или частичную адреналэктомию, не выявлено [21].…”
Section: обсуждение результатов исследованияunclassified